Konsep dan Urgensi Dasar Negara : Kedudukan Pancasila sebagai Sumber dari Segala Sumber Hukum - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiyah; Denta Rizqa Aulia Febriana; Lu’Lu’ Khairunnisa’; Arzaq Danda Iktibar Mahardika; Salsabila Khoirunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
The overarching goal of this study is to gain a deeper familiarity with Pancasila, its guiding principles, and its significance as a national framework. The theory that serves as the basis for this research's discussion is derived from the findings of literature studies conducted with a variety of existing sources, including in-depth expert journals, articles, and books. Given Pancasila's significance as a state, the author is keen on re-examining its application as the foundation of the state. This highlights the significance of Pancasila's implementation for any nation.